A violência entre as torcidas organizadas na cidade do Natal e região metropolitana e o seu uso pedagógico nas aulas de História - Bezerra, Thiago Morais (2022)
Violence is a recurring theme in History classes. It appears in the form of wars, revolts and revolutions, from the beginning of humanity to the present day. As a recurrent and present theme in the daily life of a city like Natal and the metropolitan region, I felt the lack and the need to problematize urban violence in History classes, as violence is present in the daily lives of many young people who are attending high school. Based on this need, I chose the topic of violence involving organized supporters, as a result of observation over the last decade, as some of these young people are either part of a supporter group or know someone, a friend or relative who belongs to one of these groups. We intend, with the discussions proposed in History classes, through a workshop, to denaturalize the violence practiced by organized supporters and understand it as a social problem, beyond a football stadium, and historically built from a research in newspapers local and national and a vast bibliographical reference since the year 2009. We seek to understand how this practice of violence involving young fans has increased considerably in recent years, as well as to promote, recognize and combat the various forms of inequalities and violence, adopting ethical principles , democratic, inclusive and supportive, in respect for Human Rights, with the aim of developing a culture of peace.